Complete Genome Sequence Analysis of an Imported Dengue Virus Serotype 1 Strain from Myanmar - Zeng, Zhaoping (Genome Announc, 2018)
It has been determined that recent dengue virus epidemics in Yunnan, China, originated from Southeast Asian strains. Here, we report the first complete genome sequence and molecular characterization of the imported dengue virus serotype 1 strain YNPE1. Phylogenetic analysis revealed that strain YNPE1 belonged to genotype I.